The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12933-019-0859-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between fasting plasma glucose and glycated hemoglobin in the prediabetes range and future development of hypertension

Abstract: Background: Prediabetes is a well-established risk factor for progression to overt diabetes mellitus (DM), which is in turn associated with development of hypertension (HTN) and vice versa. However, the role of prediabetes and HbA1c in particular as an independent risk factor for the development of hypertension is unclear.Aim: In this current study, we aimed to evaluate the association between both fasting plasma glucose (FPG) and hemoglobin A1c (HbA1c) levels in the prediabetes range and development of HTN am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 40 publications
(86 reference statements)
4
28
0
Order By: Relevance
“…Similar to our study ndings, several studies [16][17][18] have reported that fasting blood sugar is a predictor for future incidence of hypertension and is elevated in hypertensive patients. A higher monocyte count is a surrogate for in ammatory processes and a predictor of future hypertension as reported in one study [19].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study ndings, several studies [16][17][18] have reported that fasting blood sugar is a predictor for future incidence of hypertension and is elevated in hypertensive patients. A higher monocyte count is a surrogate for in ammatory processes and a predictor of future hypertension as reported in one study [19].…”
Section: Discussionsupporting
confidence: 92%
“…Discrepancies between HbA 1c and FPG have been reported by some studies. A study of the risk of hypertension in patients with prediabetes demonstrated the discrepancy between HbA 1c and FPG [20]. A study using data from residents of Yunnan Province, China, showed that a discrepancy between HbA 1c and FPG was present in approximately 30% of participants [21].…”
Section: Discussionmentioning
confidence: 99%
“…In a Japanese cohort study with five years of follow-up, 9,584 individuals were investigated, and elevated expressions of HbA1c were not associated with an increased risk of developing hypertension in the multivariable analysis [41]. An increment in HbA1c level was also reported not to be independently involved in the future development of hypertension among the Israeli population [42]. Kroke et al [43] revealed that there was a nonsignificant relationship between HbA1c and arterial hypertension in nondiabetic participants; nevertheless, arterial hypertension was defined as a BP of 160/95 mmHg or greater.…”
Section: Discussionmentioning
confidence: 99%